Analisis Perencanaan dan Pertanggungjawaban APBDes Menurut Peraturan Menteri dalam Negeri Nomor 20 Tahun 2018 dalam Upaya Meningkatkan Pembangunan Desa - Meira Chusnul Khotimah; Selli Dwi Parwati; Melinda Diyah Astuti; Rahma Aulia; Eva Wulandari (International Forum of Researchers and Lecturers, 2025)
Villages are autonomous regions which have special features in the form of village financial management which is described in the form of the Village Revenue and Expenditure Budget (APBDes). This research aims to analyze APBDes Planning and Accountability in Rambeanak Village, Mungkid City, Magelang Regency. The method used is descriptive qualitative and case approach as well as primary data through interviews and documentation. The research results show that APBDes planning and accountability are regulated in Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management in Rambeanak Village, which is fully implemented in accordance with existing regulations. However, the implementation of the use of the Siskeudes application with the contribution of the cash management system has not been fully realized.